Contributions of Contemporary Human Temporal Bone Histopathology to Clinical Otology. (30th July 2019) - Tucci, Debara L.; Doherty, Joni K.
Abstract : Contemporary techniques have greatly enhanced the contributions of human temporal bone (HTB) histopathology to our understanding of the mechanisms of human otologic disease and disease treatment. Herein, we review some of the most salient contributions of this research to disease management. The field of HTB histopathology is challenged by limited resources as applies to trained investigators, infrastructure, and well‐equipped laboratories. This research provides insights into clinical otology that cannot be obtained by any other means. Measures should be taken to preserve and extend the contributions of HTB research.